2009
DOI: 10.1080/87565640902801841
|View full text |Cite
|
Sign up to set email alerts
|

Reading Disabilities in SLI and Dyslexia Result From Distinct Phonological Impairments

Abstract: Children with specific language impairment (SLI) who show impaired phonological processing are at risk of developing reading disabilities, which raises the question of phonological impairment commonality between developmental dyslexia (DD) and SLI. In order to distinguish the failing phonological processes in SLI and DD, we investigated the different steps involved in speech processing going from perceptual discrimination through various aspects of phonological memory. Our results show that whereas the memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
33
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 44 publications
6
33
0
6
Order By: Relevance
“…Our results are also supported by a growing body of research in reading-impaired children and adults. Several authors have observed serial order retention deficits in poor readers (Mason, Katz, & Wicklund, 1975), in a case of developmental surface dysgraphia (Romani, Ward, & Olson, 1999) and in dyslexic children (Nithart et al, 2009) even if these studies did not explicitly distinguish between item and order STM processes. Martinez Perez, Majerus, and Poncelet (submitted for publication) used specific tasks maximizing STM for serial order or item information and observed an important impairment of order STM capacities in dyslexic adults.…”
Section: Relationship Among Phonological Processes Item Stm and Reamentioning
confidence: 97%
“…Our results are also supported by a growing body of research in reading-impaired children and adults. Several authors have observed serial order retention deficits in poor readers (Mason, Katz, & Wicklund, 1975), in a case of developmental surface dysgraphia (Romani, Ward, & Olson, 1999) and in dyslexic children (Nithart et al, 2009) even if these studies did not explicitly distinguish between item and order STM processes. Martinez Perez, Majerus, and Poncelet (submitted for publication) used specific tasks maximizing STM for serial order or item information and observed an important impairment of order STM capacities in dyslexic adults.…”
Section: Relationship Among Phonological Processes Item Stm and Reamentioning
confidence: 97%
“…LI and RD are related disorders, as both involve deficits in the integration and utilization of communicative tools. Impaired phonological skills have been implicated in both LI and RD [1][7]. LI and RD are frequently comorbid; as children with LI are at higher risk of developing RD than their typically developing peers [1][2], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Dyslexia is believed to be neurobiological in nature and is thought typically to be related to a deficit in the ability to process phonological components of language (Goswami, 2002;Ramus et al, 2003;Sprenger-Charolles & Serniclaes, 2003). Studies investigating phonological processing in dyslexic readers have focused on different constructs such as phonological memory, phonological awareness and rapid automatic naming, among others (see, for instance, Nithart et al, 2009). Spelling processes are interesting to study because, in alphabetic languages such as French and English, they rely heavily on phonological abilities.…”
Section: Introductionmentioning
confidence: 99%